A modified retinex illumination normalization approach for infant pain recognition systems - Muhamad Naufal Mansor (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2014)
In this work a novel method of illumination invariant normalization known as Modified Retinex Normalization (MRT) for preprocessing of infant face recognition is proposed. This is based on a modified retinex model that combines with histogram normalization for filtering the illumination invariant.